Les droits de superficie et l'imprécision du langage juridique - Goulet, Jean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
This comment points out a confusion among both French and Canadian authors about the real nature of the right of superficies. Under the single name of this jus in re, two institutions must be distinguished. One should more aptly be called "superficiary property" ; it bears on the upper portion of the land, excluding the soil but including a consecutive right of accession, within the meaning of art. 414 of the Civil Code. The other institution subsumed under the same name is the "right of superficies" proper, conferring ownership of the buildings or improvements made on the land, but without implying any conveyance, from the owner of the land to the beneficiary of the right of superficies, of property in the soil. In that sense, the right of superficies stands in relation to the ownership of the land as a dismemberment of that ownership, which is incomplete since the right of accession under art. 414 belongs to another party.